Screening of cervix-uterine cancer: knowledge and meaning for workers from a public nursing school - Merighi, Miriam Aparecida Barbosa; Hamano, Lina; Cavalcante, Lubiana Guilherme (Revista da Escola de Enfermagem da USP, 2002)
This is an exploratory descriptive study, carried out at a nursing school, in which 63 non-teacher workers participated. Its objectives were to check their knowledge about screening of cervix-uterine cancer and to know their feelings and expectations as they undergo this test. A questionnaire was used to collect data and the last question was recorded and analyzed using the social phenomenology theoretical framework. The answers provided information which made it possoble for us to rethink about adequate assistance guided by humanized actions considering the being in this existential entirety and belonging to a social economical cultural context.